THE RELATIONS BETWEEN REALITY AND FICTION AND THE HISTORICAL NOVEL IN A TORRE DA BARBELA, BY RUBEN A - Borborema Bozzo, Gabriela Cristina [UNESP] (Fundacao Univ Tocantins, 2021)
The relations between the real and the fictitious,as well as the possibility of an allegorical interpretation,are instigating in the novel A torre da Barbela, by Ruben A.This article investigates such relations between the real and the fictitious, as well as proposes to verify, in the novel, the possibility of an allegorical analysis. The investigations of this study were based on the readings discussed in the texts Atos de Fingir and O Imaginario (1996), by Wolfgang Iser, and O efeito do real (1972), by Roland Barthes. As for the investigation about the historical face of the novel we base ourselves on A Transfiguracao da historia em 'A Torr eda Barbela', by Maria de Fatima Marinho.
Keywords: Real; Fictitious; Imaginary; A Torre da Barbela; Historical Fiction